Evidence that an informal environmental summer camp can contribute to the construction of the conceptual understanding and situational interest of STEM in middle-school youth. Issue 3 (3rd July 2018) - Ghadiri Khanaposhtani, Maryam; Liu, ChangChia James; Gottesman, Benjamin L.; Shepardson, Daniel; Pijanowski, Bryan
ABSTRACT: Youth are introduced to STEM topics through informal settings like science camps, aquaria, and zoos. In these interactive and sensory-rich environments, a well-designed programme can help participants to acquire knowledge and cultivate interest through experiential learning. Given the importance of informal activities in environmental education, it is crucial to identify which contextual components lead to successful learning outcomes. Thus far, research in environmental STEM education has focused on brief experiences, such as one-time visits to curated environments likeaquaria. Investigating the impact of multi-day/longer experiences in natural settings is critical because the level of engagement with the STEM topic and the interaction with the learning environment in such experiences have different cognitive and affective impacts. To address these current limitations, we explored whether there is evidence that a four-day, immersive outdoor soundscape ecology camp contributed to situational interest and conceptual understanding of middle-school youth. During the soundscape camp, a variety of evidence was collected through different instruments including drawing activities, questionnaires, an interview, and field-observations. Through a qualitative analysis and open coding, we identified three core principles of informal outdoor curricular design that positively contribute to participants' learning experiences, including direct experience with nature, the use of authentic technology, and exercises that promote collaborative teamwork. We argue that activities that promote scientific practices and engagement with authentic tools in a real-world context creates a learning environment in which participants collaboratively construct deep conceptual understanding of different aspects of environmental STEM topics and foster interest in the context of science inquiry.